Identify Appropriate Variables Through Scenario Planning Perspective for Creative Tourism in Iran - MOUSAVI, Mir Najaf; GHALEHTEIMOURI, Kamran Jafarpour; SOTOUDEH, Nazanin Zahra; FAHLIANI, Mohammad Reza Amiri (Studia Universitatis Babeș-Bolyai Geographia, 2023)
This study explores the major factors affecting the creative tourism market in Iran and their potential to drive national and regional development in the long run. The study employs the MicMac and Scenario Wizard software to identify the variables and their relationships and influence on each other. The study finds that communication infrastructure is a general factor that affects all guest communities, while others are specific to capital attraction from Middle Eastern countries. These include improving political relations with these countries and digital advertising and marketing of Iran’s development. This study aimed to investigate the effectiveness of a new teaching methodology on student performance in mathematics. The methodology involved a combination of interactive lectures, group discussions, and hands-on activities. A quasi-experimental design was used, with one group of students receiving the new methodology and a control group receiving traditional teaching methods. The study was conducted over the course of one semester with pre- and post-tests administered to both groups. The results showed a significant improvement in the performance of the experimental group compared to the control group. The experimental group had a mean post-test score of 87.5, compared to the control group’s mean score of 76.2. The influence graph shows the relationships between the variables and how they influence one another, and the spatial structure of the direct driving forces of creative tourism development in Iran is indicated at a rate of 25%. This research offers insights and recommendations for policymakers, tourism practitioners, and scholars interested in the development of creative tourism in Iran. These findings suggest that the new teaching methodology can be an effective way to improve student performance in mathematics. Further research could explore the impact of this methodology on other subjects and in different settings.